Fifty years of co‐evolution and beyond: integrating co‐evolution from molecules to species. Issue 21 (21st October 2015) - Carmona, Diego; Fitzpatrick, Connor R.; Johnson, Marc T. J.
Abstract : Fifty years after Ehrlich and Raven's seminal paper, the idea of co‐evolution continues to grow as a key concept in our understanding of organic evolution. This concept has not only provided a compelling synthesis between evolutionary biology and community ecology, but has also inspired research that extends beyond its original scope. In this article, we identify unresolved questions about the co‐evolutionary process and advocate for the integration of co‐evolutionary research from molecular to interspecific interactions. We address two basic questions: (i) What is co‐evolution and how common is it? (ii) What is the unit of co‐evolution? Both questions aim to explore the heart of the co‐evolutionary process. Despite the claim that co‐evolution is ubiquitous, we argue that there is in fact little evidence to support the view that reciprocal natural selection and coadaptation are common in nature. We also challenge the traditional view that co‐evolution only occurs between traits of interacting species. Co‐evolution has the potential to explain evolutionary processes and patterns that result from intra‐ and intermolecular biochemical interactions within cells, intergenomic interactions (e.g. nuclear‐cytoplasmic) within species, as well as intergenomic interactions mediated by phenotypic traits between species. Research that bridges across these levels of organization will help to advance our understanding of the importance of the co‐evolutionary processes in shaping the diversity of life on Earth.